2023
DOI: 10.1126/sciadv.adg2248
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and viral fusogens cause neuronal and glial fusion that compromises neuronal activity

Abstract: Numerous viruses use specialized surface molecules called fusogens to enter host cells. Many of these viruses, including the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), can infect the brain and are associated with severe neurological symptoms through poorly understood mechanisms. We show that SARS-CoV-2 infection induces fusion between neurons and between neurons and glia in mouse and human brain organoids. We reveal that this is caused by the viral fusogen, as it is fully mimicked by the exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…3, Microglia), arguing that microglia are not a major target of infection. Occasional overlap (yellow) may be due to phagocytosis of debris from virus-infected cells may arise from the recently described fusion events (Martínez-Mármol et al, 2023). Despite being surrounded by infected neurons, most microglia retaining their ramified morphology, although some cells with bushy and amoeboid morphology were present (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…3, Microglia), arguing that microglia are not a major target of infection. Occasional overlap (yellow) may be due to phagocytosis of debris from virus-infected cells may arise from the recently described fusion events (Martínez-Mármol et al, 2023). Despite being surrounded by infected neurons, most microglia retaining their ramified morphology, although some cells with bushy and amoeboid morphology were present (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…For COVID-19 research, several transgenic mice models engineered with human ACE2 (hACE2) simulate varying aspects of the disease, from lethal to non-lethal infections (Muñoz-Fontela et al, 2020). Those studies revealed the neural impact of the SARS-CoV-2 virus on both neurons and non-neuronal cells in the brain (e.g., (Song et al, 2021b; Fernández-Castañeda et al, 2022), including fusion of neurons and glial cells into syncytia with pathological function (Martínez-Mármol et al, 2023a). Furthermore, studies using non-human primates showed the neuroinvasive potential of SARS-CoV-2, and that neuronal damage is greater in older animals (Beckman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies using non-human primates showed the neuroinvasive potential of SARS-CoV-2, and that neuronal damage is greater in older animals (Beckman et al, 2022). Additionally, brain organoids have provided invaluable insights into the neuroinvasive potential of the SARS-CoV-2, Zika, and Dengue virus (Abreu et al, 2018; Sutarjono, 2018; Pellegrini et al, 2020; Song et al, 2021a; Martínez-Mármol et al, 2023b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations